Evolution of Structural and Functional Diversity of Spexin in Mammalian and Non-mammalian Vertebrate Species - Lim, Chor Hong; Lee, Megan You Min; Soga, Tomoko; Parhar, Ishwar (Frontiers in Endocrinology, 2019)
Spexin (SPX) is a novel neuropeptide, which was first identified in the human genome using bioinformatics. Since then, homologues of human SPX have been identified in mammalian and non-mammalian vertebrates; chicken, anole lizard, Nile tilapia, goldfish, zebrafish and fugu. The mature sequence of SPX, NWTPQAMLYLKGAQ, is evolutionally conserved across vertebrate species, with some variation in teleost species where Ala at position 13 is substituted by Thr. The presence of a RF-amide at the C-terminal is also common across species. However, in the rat, Arg replaces His, and Gly-Arg-Arg (GRR) to Gly-His-Arg (GHR). Whether these variations contribute to changes in the function warrants further investigation. In mammals, the gene structure of SPX comprises of six exon and five intron, however, variation exists within non-mammalian species, goldfish and zebrafish have five exons while grouper has six exons. Phylogenetic and synteny analysis, reveal that SPX is grouped together with two neuropeptides, kisspeptin (KISS) and galanin (GAL) as a family of peptides with a common evolutionary ancestor. A paralog of SPX, termed SPX2 has been identified in non-mammalians but not in the mammalian genome. The synteny analysis also shows that SPX acts as a ligand for GAL receptor 2 (2a and 2b in non-mammalian vertebrates) and 3. SPX acts as a neuromodulator with multiple central and peripheral physiological roles in the regulation of insulin release, fat metabolism, feeding behavior, and reproduction. Collectively, this review provides a comprehensive overview of the evolutionary diversity as well as molecular and physiological roles of SPX in mammalian and non-mammalian vertebrate species.